PENGEMBANGAN MEDIA EDUKATIF UTAR (ULAR TANGGA PINTAR) UNTUK MENINGKATKAN HASIL BELAJAR PPKN MATERI KEBERAGAMAN BUDAYA INDONESIA PADA SISWA KELAS V DI SDN NGASINAN REMBANG - Sri Puji Astuti; Wendri Wiratsiwi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to develop educational media UTAR (Ular Tangga Pintar) as a learning tool in the subject of Pancasila and Citizenship Education (PPKn) material on Indonesian Cultural Diversity for grade V students at SDN Ngasinan Rembang. This development is motivated by low student interest and learning outcomes due to learning methods that are still dominated by lectures and limited learning media used. This research uses the ADDIE development model which includes five stages: Analysis, Design, Development, Implementation, and Evaluation. The validation results showed that UTAR media was declared valid with a score of 90% from media experts and 93% from material experts. The practicality test shows that UTAR media is very practical to use in learning, with a score of 86% teacher response and 88% student response. In addition, the results of the effectiveness test showed that there was an increase in student learning outcomes, namely the average pre-test score of 61 increased to a post-test of 89. This media is also able to increase students' motivation and active participation in the learning process. Thus, UTAR educational media is feasible to use as an alternative interactive and fun learning media to improve students' understanding and learning outcomes in Civics learning.